BCG‐induced cytokine release in bladder cancer cells is regulated by Ca2+ signaling. Issue 2 (13th December 2018) - Ibarra, Cristián; Karlsson, Marie; Codeluppi, Simone; Varas‐Godoy, Manuel; Zhang, Songbai; Louhivuori, Lauri; Mangsbo, Sara; Hosseini, Arad; Soltani, Navid; Kaba, Rahim; Kalle Lundgren, T.; Hosseini, Abolfazl; et al.
Abstract : Bacillus Calmette–Guérin (BCG) is widely used in the clinic to effectively treat superficial urinary bladder cancer. However, a significant proportion of patients who fail to respond to BCG risk cystectomy or death. Though more than 3 million cancer treatments with BCG occur annually, surprisingly little is known about the initial signaling cascades activated by BCG. Here, we report that BCG induces a rapid intracellular Ca 2+ (calcium ion) signal in bladder cancer cells that is essential for activating the transcription factor nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) and for synthesizing and secreting proinflammatory cytokines, including interleukin 8 (IL‐8). A similar Ca 2+ response was observed when cells were exposed to the supernatant of BCG. Studying cellular molecular mechanisms involved in the BCG signaling event, we found pivotal roles for phospholipase C and the Toll‐like receptor 4. Further assessment revealed that this signaling pathway induces synthesis of IL‐8, whereas exocytosis appeared to be controlled by global Ca 2+ signaling. These results shed new light on the molecular mechanisms underlying BCG treatment of bladder cancer, which can help in improving therapeutic efficacy and reducing adverse side effects. Abstract : Our data reveal the signaling pathway induced when treating bladder cancer with BCG. At the molecular level, it appears that bioactive compounds present in the supernatant of BCG interact with the Toll‐like receptor 4 (TLR4) to trigger PLC‐dependent release of Ca 2+ (calcium ion) from ER, which subsequently activates NF‐κB (nuclear factor kappa‐light‐chain‐enhancer of activated B cells). NF‐κB triggers the synthesis of IL‐8, whereas cytosolic Ca 2+ stimulates exocytosis of IL‐8.